Avifauna de uma área urbana no Nordeste brasileiro - Moreira, André Lucas de Oliveira (2013)
Urbanization is a process responsible for environmental disturbances that occur at various levels, resulting in changing patterns of biodiversity. However, little is known about the resistance, functional diversity and ecological processes that structure communities of birds in urban environments. The present study aimed to investigate the species richness, functional diversity, resistance and ecological process that determines the assembly of communities and define diversity patterns of six bird communities in urban environment. This study was conducted in six different sizes with green areas and inserted into the urban matrix, in the city of Aracaju, Sergipe, northeastern Brazil. The tree density of the study areas were measured by counting the trees with a diameter greater than 50 mm to investigate its relation to bird diversity. The richness, composition and frequency of occurrence of the species were investigated between September 2011 and July 2012, using the method lists Mackinnon, adapted to 10 species. The sampling effort resulted in a total of 720 listings - 120 lists each area. 82 species of birds were observed and divided into 36 families. The richness of bird species increased due to the increased size of woodlands. The increase in tree density was also associated with increased species richness of birds. However, the functional richness (Fric) decreased with the increase in species richness. This study demonstrates that communities have the richest bird species with similar functions. They are functionally redundant and more resistant to environmental disturbances. It is also possible that the homogenization of bird communities in urban environments occurs through the filtering process of habitat that should structure these communities on a local scale. The environmental filters should favor the occurrence of species with certain functional characteristics and may limit the occurrence of species with distinct characteristics.